Mapping of quantitative trait loci for sheath blight resistance in rice - Mandal, Lincoln; Verma, Sunil Kumar; Kotasthane, Anil S; Agrawal, Toshy; Jalamkar, Prafull; Verulkar, Satish B (ORYZA-An International Journal of Rice, 2018)
Sheath blight is a fungal disease caused by Rhizoctonia solani Kühn, major diseases of rice and severely impairs both yields and quality. Quantitative trait loci (QTL) analysis of the sheath blight resistant using SSR markers was conducted in RIL population derived from the cross Danteshwari and Dagad deshi. Sheath blight resistant in this population and parents was screened by inoculation of fungus Rhizoctonia solani isolate in field condition. The sheath blight disease index of RIL was continuously distributed, as expected for a quantitative trait. On the basis of disease evaluations, quantitative trait loci (QTL) were identified for sheath blight resistance on chromosomes 1, 2, 3, 4, 5, 6, 8, 9, 11 and 12. The QTL, (qSBR1-1) for individual lesion length (ILL) mapped on chromosome 1. Two other QTLs, (qSBR1-1) and (qSBR1-2) for individual lesion width (ILW) were mapped to closely linked markers RM5 and RM84, respectively. The major QTL, (qSBR4-1) for total lesion length (TLL), Total lesion area (TLA) and (qSBR5-1, qSBR5-2) for total lesion area (TLA) were mapped on chromosome 4 and 5, respectively. Similarly, QTL (qSBR9-1) was mapped for individual lesion area (ILA) on chromosome 9 and (qSBR12-1) for individual lesion width (ILW) on chromosome 12, respectively. There was many minor effect QTLs also identified on various chromosome. These major QTLs will be good candidates for marker-assisted selection programme and fine mapping could lead to identification of novel resistance alleles.